THE EFFECT OF STRATEGIC FLEXIBILITY AS APPROACH TO ACHIEVE THE SUSTAINABLE COMPETITIVE ADVANTAGE THROUGH AN ANALYTICAL STUDY FOR OPINIONS OF ASIACELL MANAGERS IN IRAQ - Mohammed, Eman Basheer; Mahmood, Dalal Shikir (Journal of Duhok University, 2018)
The current study aimed to identify the effect of strategic flexibility as approach to achieve the sustainable competitive advantage through an analytical study for opinions of Asiacell managers in Iraq. The study problem focused on that to which range the strategic flexibility impact in achieving sustainable competitive advantage. Based on that, a hypothetical model was designed to reflect the correlation and effect relationships between the main factors of study and their dimensions. A group of hypotheses were emerged from the model that reflects these relationships. The study sample included 80 persons, and the questionnaire was the essential instrument to collect the data. Statistical Package for the Social Sciences (SPSS) was used to analyze the data. The main results of study were:There are high level of significant correlation between the strategic flexibility and sustainable competitive advantage. The focus of company on the strategic flexibility leads to enhance the competitive advantage through the service that provides to the customers in compare with competitors.The strategic flexibility and their dimensions (speed, innovative, agility, and alignment) affect the sustainable competitive advantage. Agility, innovative, and alignment was the most important dimensions of strategic flexibility.